Construction of nursing-sensitive quality indicators for the care of patients with prone position ventilation using the Delphi method - Xiuwen Chen; Peng Liao; Yang Zhou (BMC, 2023)
Abstract Background Prone position ventilation (PPV) has gradually become an adjuvant treatment to improve oxygenation in patients with acute respiratory distress syndrome. Scientific and comprehensive evaluation of the quality of nursing care for patients with PPV is of great significance to ensure the effectiveness of treatment and patient safety. However, there are no established objective indicators for evaluating the quality of nursing care for patients with PPV. This study intended to identify a set of scientific, systematic and clinically applicable nursing-sensitive quality indicators for the care of patients with PPV. Methods Based on the Donabedian structure-process-result theory model, the quality evaluation indicators of nursing care for patients with PPV were preliminarily constructed based on an evidence-based perspective, and two rounds of Delphi surveys were conducted with the purpose of collecting opinions from a panel of independent experts. Results The questionnaire recovery rates of the two rounds of correspondence were 100.00% and 95.00%, the recovery rates of expert opinions were 80.00% and 26.32%, the expert authority coefficient values were 0.89, and the Kendall coordination coefficient W values were 0.110 and 0.133, respectively. The final nursing-sensitive quality indicators for the care of patients with PPV included 3 first-level indicators, 9 s-level indicators and 29 third-level indicators. Conclusion The constructed nursing-sensitive quality indicators for the care of patients with PPV involve quality supervision during the whole process of PPV from three dimensions: structure, process and results. These indicators have strong operability, reliability, practicability and scientificity and can provide a reference for the quality evaluation and monitoring of nursing care for patients with PPV. Implications for nursing management The quality indicators of nursing care for patients with PPV constructed in this research are scientific and reliable, and the content of the quality indicators can better reflect the technical characteristics of special nursing. Nursing managers are encouraged to use these quality indicators to evaluate the quality of clinical nursing care and improve safety for patients with PPV.